FINITE ELEMENT NUMERIC SIMULATION FOR TEETH BUCKET EXCAVATOR INTERACTION WITH MATERIAL FOR DIGGING ACTIVITIES OF CLAY, SILT, AND SAND - Anugrah, Alfan
The digging force required by an excavator to break a material depends on the type of material to be excavated, because each material has different properties and conditions. Modelling the interaction of the teeth bucket excavator with the material can be simulated numerically using the two-dimensional finite element method using Phase2 software by taking into account the strength reduction factor and strength factor parameters. The modeling was carried out in two scenarios, namely, on a flat location and on a slope-shaped location with clay, sand, and silt materials. The critical value of SRF will decrease as the digging force increases, in scenario 1 the clay material will be break with a digging force of 77.1 kN while sand and silt material at a digging force of 25.7 kN, while for scenario 2 all materials will be break with a digging force of 25, 7 kN. There is an estimate of the failure volume for each material due to the given digging force, for clay the failure volume is 0.009 to 0.92 m3, for sand the failure volume is 0.04 to 3.55 m3. for silt the failure volume is 0.15 to 6.62 m3. In scenario 1 the specific energy in the lowest clay is 300.03 kJ/m3, the lowest specific energy in sand is 115.22 kJ/m3, the specific energy in the lowest silt is 69.53 kJ/m3. While in scenario 2 the lowest specific energy in clay is 245.75 kJ/m3, the lowest specific energy in sand is 127.02 kJ/m3, the lowest specific energy in silt is 100.95 kJ/m3.